1997
DOI: 10.1089/tmj.1.1997.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Telemedicine Examination

Abstract: On the basis of these observations and the methods used, reliability varied with the type of examination, clinician experience with telemedicine, and participant knowledge of system limitations. Clinicians without experience or knowledge of system limitations missed findings of clinical importance. Improvements in equipment since the clinics were conducted in 1994 may have resolved some of these problems. Our findings raise doubts about the reliability of occasional telemedicine consultations by clinicians ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 27 publications
2
49
0
2
Order By: Relevance
“…13 With the adoption of new technology in clinical practice, it is important that the clinician has a good understanding of the strengths and weaknesses of the equipment being used. Nitzkin et al 14 reported that practitioners with little experience of TM and a poor knowledge of the limitations of the systems in use were more likely to miss important clinical findings. A number of studies have examined the limitations associated with the use of TM in various ophthalmic subspecialties.…”
Section: Discussionmentioning
confidence: 99%
“…13 With the adoption of new technology in clinical practice, it is important that the clinician has a good understanding of the strengths and weaknesses of the equipment being used. Nitzkin et al 14 reported that practitioners with little experience of TM and a poor knowledge of the limitations of the systems in use were more likely to miss important clinical findings. A number of studies have examined the limitations associated with the use of TM in various ophthalmic subspecialties.…”
Section: Discussionmentioning
confidence: 99%
“…9 If telemedicine is to be incorporated into a protocol for follow up of pressure equalization tube surgery, then it needs to be established that video otoscope images are an acceptable replacement for the in-person microscope examination. Some studies have adequately addressed image quality and diagnostic accuracy using inter-provider and intra-provider comparisons in the fields of teleophthalmology [10][11][12][13][14][15] and teledermatology. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Few studies have addressed visualization and image capture in the other telemedicine specialties.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical reliability of the technology has been established 11. A recent systematic review commented on the poor quality of studies on the economic effectiveness of telemedicine and found no evidence that telemedicine was cost effective 12.…”
Section: Introductionmentioning
confidence: 99%